ALGORITHM OF A DIFFERENTIATED APPROACH TO MANAGEMENT OF PERSISTENT PULMONARY HYPERTENSION IN PREMATURE INFANTS - Т. Клименко; М. Кононович (Bukovynian State Medical University, 2023)
Introduction. Oxidative stress (OS) is recognized as a contributing factor to the development of persistent pulmonary hypertension (PPH) in premature infants. In the modern scientific literature, there is a lack of unequivocal recommendations for the management of PPH, considering the levels of OS, what determines the need for the development of a differentiated approach for management to infants with pulmonary hypertension. The aim of the study. To increase the efficacy of management of premature infants with persistent pulmonary hypertension with asphyxia and respiratory distress syndrome based on the development of the algorithm of a differentiated approach for management of pulmonary hypertension considering the levels of oxidative stress as determined by the urinary 8-hydroxy-2-deoxyguanosine (8-OHdG). Material and methods. Were analyzed the observations of 96 infants born prematurely at gestational age of 26/1-34/6 weeks: group I consisted of 50 infants with respiratory distress syndrome (RDS), group II - 50 infants with RDS associated with perinatal asphyxia. PPH was determined by echocardiography on the 1st and on the 3rd-5th day of life, and quantitative determination of the urinary 8-OHdG (ng/ml) was performed on 44 neonates on the 1st and in dynamics on the 3rd-5th day of life using enzyme-linked immunosorbent assay (ELISA). For comprehensive radiographic assessment of PPH, all infants received chest X-Ray with determination of Moore's, Schwedel's, and cardiothoracic indexes (CTI). Statistical analysis was performed using Microsoft Excel 2019 software. Under the conditions of normal distribution of quantities, parametric statistical methods were used to calculate the arithmetic mean (M) and the representativeness error of the mean (m). Using Fisher`s exact test (φ) we analyzed the quantitative parameters. Using the heterogeneous sequential Wald procedure, development of diagnostic criteria was performed. The essence of the procedure is to determine both diagnostic (DC), prognostic coefficients (PC) and diagnostic informativeness (I) of the investigated indicators. The minimum informativeness of the feature required for addition to the developed algorithm was considered I ≥ 0.25. The algorithm was developed on the basis of diagnostic coefficients of clinical and anamnestic data of the examined groups of children, echocardiographic criteria for the presence and determination of the degree of PPH, the dynamics of OS levels and their comparison with the indicators of a comprehensive radiological assessment of pulmonary hypertension in prematurely born infants with RDS and perinatal asphyxia in association with RDS in gestational age of 26-34 weeks. Design of a study was discussed and approved at a session of the Ethical commission of the Kharkiv Medical Academy of Postgraduate Education (Prot. № 5 from 18.12.2020). All parents gave an informed consent for examination of their children. The study was carried out in accordance to the plan of the research work of the Department of Neonatology of the Kharkiv Medical Academy of Postgraduate Education "Study of features of the course of oxidative stress diseases in newborns" (January 2022 - December 2024), state registration number 0122U000025. Results. Has been developed an algorithm of a differentiated approach to management of premature infants with RDS and asphyxia with PPH, the essence of which - is to improve and individualize the method of mechanical lung ventilation (MLV) for each individual case. Conclusions. For prematurely born infants at gestational age 26-34 weeks, is important to determine the level of the urinary 8-OHdG on the 1st and 3rd-5th days of life to decide the severity of OS. For management of newborns with PPH, in the case of an increase of the level of 8-OHdG by the 3rd-5th day of life, is recommended to increase the ventilator parameters; in the case of a decrease - diminish the ventilation parameters or extubate an infant.